2019
DOI: 10.1108/josm-11-2018-0376
|View full text |Cite
|
Sign up to set email alerts
|

Social innovation in service: a conceptual framework and research agenda

Abstract: Purpose The purpose of this paper is to provide a framework for guiding social innovation in service (SIS), defined as the creation of novel, scalable and sustainable market based service offerings that solve systemic societal problems. Design/methodology/approach This research provides a review and synthesis of transdisciplinary literatures to establish a basis for the conceptual framework proposed for SIS. Findings It is argued that the primary unit of an SIS is the service firm and that there are micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 77 publications
3
99
0
1
Order By: Relevance
“…What we maintain is that, after a first part characterized by the necessity to increase the community of users, the trust in the platform, and communicate the value propositions, MSPs have to face the negative effects of their growth. In order to do so, we showed that MSPs leverage and implement social innovations to face these challenges, thus moving toward a sustainable BM, as the general management literature has started to highlight (Aksoy et al, 2019). These findings are in line with Randle and Dolnicar (2019) who maintain that Airbnb has been able to cause disruption not only to the hospitality industry, but also to the society as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What we maintain is that, after a first part characterized by the necessity to increase the community of users, the trust in the platform, and communicate the value propositions, MSPs have to face the negative effects of their growth. In order to do so, we showed that MSPs leverage and implement social innovations to face these challenges, thus moving toward a sustainable BM, as the general management literature has started to highlight (Aksoy et al, 2019). These findings are in line with Randle and Dolnicar (2019) who maintain that Airbnb has been able to cause disruption not only to the hospitality industry, but also to the society as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Aksoy et al (2019) go further and introduce the concept of SI as a specific approach that assumes as fundamental the creation of novel and scalable solutions that solve systemic societal issues. Specifically, there is a call for exploring and finding new products/services, new ways to meet social needs, empowering people, and creating new social relationships and collaboration approaches (European Union and The Young Foundation, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sustainable Development Goals (SDGs) in the 2030 Agenda point out the importance of innovation, and even more so grounded in a social sphere, because it faces the various challenges to accelerate progress and contribute to ending poverty and poverty. hunger; guarantee inclusive health and education; achieve gender equality, sustainability, and climate action; support action and innovation at the local level (Aksoy, Alkire (né e Nasr), Choi, Kim, & Zhang, 2019;Naciones Unidas, 2020a). Similarly, the 2030 Agenda indicates that innovation is a requirement of "transformation of the financial, economic and political systems that govern our societies today to guarantee the human rights of all" (United Nations, 2020b, p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, not only the collaboration of the government is required, but also the participation of the companies that attribute the main activities of production and consumption of products and services. (Aksoy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%